Chronic pain prevalence and associated factors in adolescents with and without physical disabilities. - De la Vega, Rocío; Groenewald, Cornelius; Bromberg, Maggie H.; Beals-Erickson, Sarah E.; Palermo, Tonya M. (Wiley, 2018)
AIM Adolescents with physical disabilities may have co-occurring chronic pain, but the prevalence and specific associated factors are unknown. The aims of this study were to determine (1) the prevalence of chronic pain in adolescents with physical disabilities and (2) whether known correlates of chronic pain in the general population are also present in young people both with physical disability and with chronic pain relative to peers. METHOD We conducted a secondary analysis of cross-sectional nationally representative data from the National Longitudinal Study of Adolescent to Adult Health. Multivariate linear regression analysis was used to identify demographic and psychosocial factors associated with chronic pain. RESULTS A total of 989 (4.3%) adolescents reported physical disabilities. They had a significantly higher rate of pain (27.2%) compared with able-bodied peers (15.6%, v2 =86.3550, p<0.001). There was no significant interaction between physical disability status and chronic pain in relation to depressive symptoms, anxiety, or insomnia. INTERPRETATION Adolescents with physical disabilities experience chronic pain at a significantly higher rate than able-bodied peers, but the comorbidity of physical disability and chronic pain is not related to depression, anxiety, or insomnia. Evaluation of chronic pain and tailored pain interventions need to be developed for this population.
Es una versión preprint. https://openpolicyfinder.jisc.ac.uk/id/publication/7644
Keywords: Dolor crónico; Adolescentes; Chronic pain; Adolescents